P69 Inquiry of social media use in adolescents assessed in a camhs clinic in UK. (18th November 2019) - James, C; Shetty, V
Abstract : Aims: The Royal College of Paediatrics and Child Health (RCPCH) published guidelines (in 2019) for parents and clinicians on screen time for children and young people. The impact of social media use on a young person's physical and mental health is currently being researched. We are aware of the positive and negative effects of social media use on mental health. Negative effects can include body-image disturbances, cyberbullying, poor sleep, mood disturbances and anxiety. The aim of the audit was to investigate whether social media usage was considered during an initial assessment (and risk assessment) of a young person in a CAMHS clinic in UK. Methods: An Audit was completed at 3 different CAMHS clinics over a 2 month period for all initial assessments. Electronic case records (nationally used) were checked. Total number of cases reviewed were 150. The authors devised a data collection tool to check for evidence of questions asked in relation to social media usage. A survey of all CAMHS professionals in the region was also completed to enquire if they routinely asked questions in relation to screen time and social media use during initial assessment. Results: The audit showed less than 5% of young people assessed in clinics over a 3 month period were routinely asked about their social media use during their initial assessment. Moreover, there was no proportional increase in enquiry for 'high risk' cases. The results are likely to be applicable County-wide as a single electronic record system is used. The survey showed that social media use and associated risks were not routinely enquired. Furthermore, there were no prompts on the electronic assessment tools for professionals. Conclusions: The audit demonstrated a significantly low (almost negligent) percentage of young people (or their parents) actively asked about social media use and its impact on their mental health. Given the likely effects especially in a vulnerable population, it is important these are asked routinely. The authors devised a simple screening tool to be part of the assessment tool on the electronic records. Local teaching sessions were also arranged with clinicians and parent workshops were organised. A re-audit will be completed to evaluate the impact of the training and workshops.